Pengembangan Model Latihan Passing Segitiga Jarum Jam (SJJ) Ekstrakulikuler Futsal SMA Negeri 2 Sungai Lilin - Billi Al Mukminin; Farizal Imansyah; Taheri Akbar (Journal on Education, 2023)
This study aims to produce a clockwise triangle (SJJ) passing training model for futsal players in the final product in the form of a book that can make it easier to learn and practice doing the SJJ training model movements.This type of research is research and development (Reseach & Development). This research is carried out through the stages of: 1) potential problems, 2) data collection, 3) product design, 4) expert validation, 5) product revision, 6) product trials, and 7) final product. This research produces products that are validated by material experts and media experts. The resulting product was tested on extracurricular futsal players at Sungai Lilin 2 Public High School through product trials. The test subject was an extracurricular futsal player at SMA Negeri 2 Sungai Lilin. Data analysis techniques use quantitative data in the form of scores converted into percentages. Material expert validation data results get a percentage of 96%. According to media experts, the percentage is 87%. From the trial data the large group got a percentage of 90.2%. The results of this study were the product of the extracurricular futsal extracurricular clockwise triangle passing (SJJ) model at SMA Negeri 2 Sungai Lilin which is "very good" or very suitable for use as material for training models in practice